Characterising the safety of clomiphene citrate in male patients through prostate‐specific antigen, haematocrit, and testosterone levels. (24th June 2016) - Chandrapal, Jason C.; Nielson, Spencer; Patel, Darshan P.; Zhang, Chong; Presson, Angela P.; Brant, William O.; Myers, Jeremy B.; Hotaling, James M.
Abstract : Objective: To determine the safety profile of clomiphene citrate (CC) in men being treated for hypogonadism or infertility by measuring prostate‐specific antigen (PSA), haematocrit (Hct), and testosterone levels. Patients and Methods: We identified patients presenting to our institution who were placed on CC, 50 mg every day or every other day, for male infertility and/or symptomatic hypoandrogenism between September 2013 and April 2016. Patients with documented exogenous testosterone, human chorionic gonadotrophin, or anastrozole use within 2 weeks of baseline evaluations were excluded. Our primary outcomes were the effects of CC on PSA, Hct, and total testosterone levels evaluated at the 3, 6, 9, or 12 months of follow‐up. Outcomes were averaged within patients across visits and summarised by mean, median, range, standard deviation (SD) and the 95% confidence interval (CI) for the mean. Results: A total of 77 patients had recorded PSA, Hct, and/or testosterone values. The mean (SD, range) age and body mass index was 34 (6, 22–51) years and 31 (6, 22–52) kg/m 2, respectively. The mean (SD) follow‐up was 358 (29) days. Within this group, CC concentration was changed in 24 patients (31%) and was discontinued in 24 patients (31%). The median (range) duration of CC therapy before discontinuation was 127 (44–161) days. The use of CC significantly raised both mean total and bioavailable testosterone levels by 200 ng/dL and 126 ng/dL, respectively ( P < 0.001). This increase in testosterone had significant clinical effects with improvements in Androgen Deficiency in Aging Male questionnaire scores ( P < 0.01) but not Sexual Health Inventory for Men scores. CC had no effect on mean PSA (1 ng/dL, 95% CI 0.8–1.1) or Hct (49%, 95% CI 41–53) levels, which were within normal ranges. Conclusions: As more men are placed on CC for infertility or hypogonadism, characterising the safety effect profile becomes important. Our study found that CC significantly increased testosterone levels without changing PSA or Hct values. Because the biochemical response to CC can vary, we suggest scheduling laboratory evaluation at regular intervals; however, ordering routine assessment of PSA and Hct may not be necessary.